THE EFFECTS OF CONE-BEAM COMPUTED TOMOGRAPHY IMAGING GUIDANCE ON PATIENT RADIATION EXPOSURES IN TRANS-ARTERIAL CHEMOEMBOLISATION FOR HEPATOCELLULAR CARCINOMA. Issue 8 (30th May 2022) - Wong, S Y; Foley, S; Cantwell, C P; Ryan, R; Lucey, J; Maher, P; McNulty, J P
Abstract: This study investigated the effects of cone-beam computed tomography (CBCT) guidance in trans-arterial chemoembolisation (TACE) procedures on the number of digital subtraction angiography (DSA) runs acquired and total patient radiation exposure in patients with hepatocellular carcinoma (HCC). A retrospective, analytical cross-sectional, single institution, study was conducted. Dose data were compared across the control (DSA guidance alone) and study (DSA and CBCT guidance) groups. A total of 122 procedures were included within the study. There was a significant reduction in the number of DSA runs (3 vs 5, p < 0.001 ) and DSA air kerma-area product (PKA) (3077.3 vs 4276.6 μGym 2, p = 0.042 ) for the study group when compared to the control group. Total procedural PKA and total procedural reference air kerma (Ka, r ) were shown to be 50 and 73% higher, respectively, for the study group when compared to the control group. CBCT imaging guidance does reduce the number of DSA runs and DSA PKA required to complete the TACE procedure for patients diagnosed with HCC; however, a substantial increase in total procedural PKA is to be expected and it is thus important that this increased dose is carefully considered and justified.